Peran Kompetensi Profesional Guru terhadap Kemampuan Berpikir Kritis Siswa di MI Islamiyah Paweden - Firman Syah, Wahyu; Jaeni, Muhamad (Indonesian Journal of Islamic Elementary Education, 2023)
Teacher professional competence includes mastery of the material, understanding of students, educational learning, personal development, and mastery of the material. Critical thinking skills play an important role in the decision-making process to solve problems so it is important for students to have. Based on this background, this study aims to: 1. describe the professional competence of teachers at MI Islamiyah Paweden; 2. describe students' critical thinking skills at MI Islamiyah Paweden; 3. Describe the role of teacher professional competence in students' critical thinking skills at MI Islamiyah Paweden. This type of research is field research. The approach used in this study is a descriptive qualitative approach. Collecting data in this study using the method of observation, interviews, and documentation. The results of the study show that: 1) teachers at MI Islamiyah Paweden mostly have fulfilled professional competence but have not fully met the criteria; 2) students' critical thinking skills are quite good in solving a problem, the ability to select information, the ability to identify assumptions, the ability to formulate hypotheses, and the ability to draw conclusions; 3) the role of teacher professional competence on students’critical thinking skills through various teaching methods, providing stimulus, and discussion.